Demographic Analysis of a Declining Northern Bobwhite Population in Southwestern Ohio - Robert J. Gates; Adam K. Janke; Marjorie R. Liberati; Mark J. Wiley (National Quail Symposium Proceedings, 2017)
Northern bobwhite (Colinus virginianus) populations continue to decline throughout much of their range, especially in the Midwestern United States. Land use and habitat changes are understood to be the primary cause of decline, and it is unclear how vital rates affect growth of regional populations. We estimated relative abundance and population vital rates of bobwhites on 8 private land sites in southwestern Ohio during 2008–2011. Life stage simulation analyses were used to model the influence of 9 demographic parameters on population growth rates (k). All but one vital rate, chick survival, were modeled with empirical data randomly selected from normal distributions estimated (mean 6 SD) from our study population. The median value of k after 1,000 simulations was 0.248 (inter- quartile range 1⁄4 0.113-0.428). Non-breeding season survival was the dominant vital rate, explaining 50.4% of variation in k, followed by nest success (r2 1⁄4 0.163), and breeding season survival of adults (r2 1⁄4 0.083). Chick survival, egg success, and clutch size individually explained in order 1.4 to 4.6% of variation in k when modeled with survival estimates. Renesting, double-brooding, and male incubation individually explained , 1% of the variation in k. Total fecundity modeled as the sum across individual vital rate components explained 36.9% of variation in k. Non-breeding season survival was the most limiting population vital rate, but age ratios of fall-captured birds and simulated fecundity values indicated partial limitation by recruitment. Population stability (k 1⁄4 1) could be achieved by increasing non-breeding survival from 10.9 to 36.9%. Higher rates of nest success, the second most limiting vital rate, would not stabilize population growth unless survival rates also increased. Bobwhite conservation strategies should emphasize habitat enhancements designed to increase survival rates and useable space during the non-breeding season in Ohio and possibly other Midwestern states.
Keywords: Colinus virginianus; fecundity; life stage simulation; nesting; northern bobwhite; Ohio; population; survival; vital rate